The Effect of Motivation, Supervision, and Patient Safety Training on the Implementation of Patient Safety Culture in Hospitals - Wa Ode Nelly Estika; Wahyuni Dian; Erry Yudha (Indonesian Journal Publisher, 2026)
Background:The implementation of patient safety culture by nurses reflects their performance behavior and is influenced by nurses’ motivation. With good motivation, nurses are expected to effectively apply patient safety culture. Nursing supervision activities are carried out in accordance with hospital nursing management guidelines.Objective:This study aimed to determine the effect of motivation, supervision, and training on the implementation of patient safety culture in hospitals.Methods:This study adopted a quantitative research approach with a cross-sectional design. The population consisted of all nurses working in inpatient units at Dr. R. Soedjono Selong Regional General Hospital, totaling 415 nurses. A sample of 204 nurses was selected for the study. Data analysis was conducted using path analysis to examine the proposed model, and the relationships among constructs were assessed by evaluating the path coefficients.Results:Motivation (p-value = 0.003 < 0.005), supervision (p-value = 0.000 < 0.005), and nurse training (p-value = 0.001 < 0.005) had a positive and significant effect on the implementation of patient safety culture in hospitals. Conclusion:Nurses’ motivation, supervision, and training have a positive and significant effect on the implementation of patient safety culture in hospitals.